2022
DOI: 10.1111/tpj.15920
|View full text |Cite
|
Sign up to set email alerts
|

The histidine phosphotransfer AHP4 plays a negative role in Arabidopsis plant response to drought

Abstract: Cytokinin plays an important role in plant stress responses via a multistep signaling pathway, involving the histidine phosphotransfer proteins (HPs). In Arabidopsis thaliana, the AHP2, AHP3 and AHP5 proteins are known to affect drought responses; however, the role of AHP4 in drought adaptation remains undetermined. In the present study, using a loss-of-function approach we showed that AHP4 possesses an important role in the response of Arabidopsis to drought. This is evidenced by the higher survival rates of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 157 publications
0
6
0
Order By: Relevance
“…The findings demonstrated for the first time that AHK4 was capable of interacting with AHP1, 2, 3, and 5 via a close phosphorelay reaction (Suzuki et al, 2001). Studies in Arabidopsis showed that the reaction to drought is negatively impacted by the histidine phosphotransfer AHP4 (Ha et al, 2022), AHP1, AHP2, AHP3, and AHP5 can communicate with AHK2, AHK3, and AHK4 (Dortay et al, 2006; Mähönen et al, 2006), and histidine phosphotransfer proteins from Arabidopsis AHP2, AHP3, and AHP5 serve as redundant negative regulators of the drought stress response (Nishiyama et al, 2013). This indicates that GhHK8 may participate in cotton drought control…”
Section: Resultsmentioning
confidence: 99%
“…The findings demonstrated for the first time that AHK4 was capable of interacting with AHP1, 2, 3, and 5 via a close phosphorelay reaction (Suzuki et al, 2001). Studies in Arabidopsis showed that the reaction to drought is negatively impacted by the histidine phosphotransfer AHP4 (Ha et al, 2022), AHP1, AHP2, AHP3, and AHP5 can communicate with AHK2, AHK3, and AHK4 (Dortay et al, 2006; Mähönen et al, 2006), and histidine phosphotransfer proteins from Arabidopsis AHP2, AHP3, and AHP5 serve as redundant negative regulators of the drought stress response (Nishiyama et al, 2013). This indicates that GhHK8 may participate in cotton drought control…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, an auxin efflux carrier and the ARF TF Monopteros , which inhibits stomatal development ( Zhang et al , 2014 ), were found among the NAC61 HCTs. Similarly, the down-regulation of the HCTs histidine phosphotransfer AHP4 , whose knockout narrows stomatal apertures, heightens leaf temperatures during water stress, and increases leaf RWC ( Ha et al , 2022 ), and the phosphatase PP2CA/AHG3 , whose repression activates ABA-mediated signaling pathway leading to stomatal closure and water retention ( Jung et al , 2020 ), may contribute to NAC61 function in osmotic stress responses. Interestingly, hypoxia-related genes are found among NAC61- induced DEGs, such as a Hypoxia-responsive gene and three dehydration-responsive proteins ( RD22 ), indicating a decrease in oxygen supply, likely due to water saturation of the apoplast ( van den Dries et al , 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, an auxin efflux carrier and the ARF TF Monopteros, which inhibits stomatal development (Zhang et al, 2014), is found among NAC61 HCTs. Similarly, the downregulation of the HCTs histidine phosphotransfer AHP4, whose knock-out narrows stomatal apertures, heightens leaf temperatures during water stress and increases leaf RWC (Ha et al, 2022) and the phosphatase PP2CA/AHG3, whose repression activates ABA-mediated signaling pathway leading to stomatal closure and water retention (Jung et al, 2020), may contribute to NAC61 function in osmotic stress responses. Interestingly, hypoxia-related genes are found among NAC61 induced DEGs, such as a Hypoxia-responsive gene and three dehydration-responsive proteins (RD22), indicating a decrease in oxygen supply likely due to water saturation of the apoplast (van den Dries et al, 2013).…”
Section: Nac61 Is Responsive To Osmotic Stressmentioning
confidence: 99%